Lactic acid production from submerged fermentation of broken rice using undefined mixed culture - Nunes, Luiza Varela [UNESP]; Barros Correa, Fabiane Fernanda de [UNESP]; Oliva Neto, Pedro de [UNESP]; Malacrida Mayer, Cassia Roberta [UNESP]; Escaramboni, Bruna [UNESP]; Campioni, Tania Sila [UNESP]; Barros, Natan Roberto de [UNESP]; Herculano, Rondinelli Donizetti [UNESP]; Fernandez Nunez, Eutimio Gustavo [UNESP] (Springer, 2017)
The present work aimed to characterize and optimize the submerged fermentation of broken rice for lactic acid (LA) production using undefined mixed culture from dewatered activated sludge. A microorganism with amylolytic activity, which also produces LA, Lactobacillus amylovorus, was used as a control to assess the extent of mixed culture on LA yield. Three level full factorial designs were performed to optimize and define the influence of fermentation temperature (20-50 degrees C), gelatinization time (30-60 min) and broken rice concentration in culture medium (40-80 g-L-1) on LA production in pure and undefined mixed culture. LA production in mixed culture (9.76 g-L-1) increased in sixfold respect to pure culture in optimal assessed experimental conditions. The optimal conditions for maximizing LA yield in mixed culture bioprocess were 31 degrees C temperature, 45 min gelatinization time and 79 g-L-1 broken rice concentration in culture medium. This study demonstrated the positive effect of undefined mixed culture from dewatered activated sludge to produce LA from culture medium formulated with broken rice. In addition, this work establishes the basis for an efficient and low-cost bioprocess to manufacture LA from this booming agro-industrial by-product.
Keywords: Activated sludge; Broken rice; Lactic acid; Mixed culture; Lactobacillus amylovorus; Three-level factorial design